2010
DOI: 10.1029/2009jf001549
|View full text |Cite
|
Sign up to set email alerts
|

Lattice‐Boltzmann modeling of the air permeability of polar firn

Abstract: [1] Recent advances in three-dimensional (3D) imaging of snow and firn combined with numerical modeling of flow through complex geometries have greatly improved the ability to predict permeability values based on microstructure. In this work, we combined 3D reconstructions of polar firn microstructure obtained from microcomputed tomography (mCT) and a 3D lattice-Boltzmann (LB) model of air flow. We compared the modeled results to measurements of permeability for polar firn with a wide range of grain and pore-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 46 publications
(73 reference statements)
2
45
0
Order By: Relevance
“…Larger permeability on a 10 m scale than a 1 m scale would occur if, for example, fractures began to exert an influence on infiltration at the larger scale. The permeabilities inferred by our measurements are 1-2 orders of magnitude smaller than permeabilities of nearsurface snow and firn (e.g., Sommerfeld and Rocchio, 1993;Campbell et al, 2006;Courville et al, 2010), values often employed for Darcy flow at the base of a snowpack or firn layer in the upper ablation zone (Arnold et al, 1998). Our measurements are, however, similar to the ∼ 0.1-0.3 m scale of near-surface permeability measurements of sea ice at temperate latitudes (Kawamura et al, 2006) and, appropriately scaled, similar to hydraulic conductivities of firn reported by Schneider (1999).…”
Section: Discussionmentioning
confidence: 85%
“…Larger permeability on a 10 m scale than a 1 m scale would occur if, for example, fractures began to exert an influence on infiltration at the larger scale. The permeabilities inferred by our measurements are 1-2 orders of magnitude smaller than permeabilities of nearsurface snow and firn (e.g., Sommerfeld and Rocchio, 1993;Campbell et al, 2006;Courville et al, 2010), values often employed for Darcy flow at the base of a snowpack or firn layer in the upper ablation zone (Arnold et al, 1998). Our measurements are, however, similar to the ∼ 0.1-0.3 m scale of near-surface permeability measurements of sea ice at temperate latitudes (Kawamura et al, 2006) and, appropriately scaled, similar to hydraulic conductivities of firn reported by Schneider (1999).…”
Section: Discussionmentioning
confidence: 85%
“…This effort has already started for modeling based on X-ray tomography images, whether for physical effective properties (Freitag et al, 2002;Courville et al, 2010) or for snow mechanics (Wautier et al, 2015;Rolland du Roscoat et al, 2007). For example, Freitag et al (2002) and Courville et al (2010) modeled the firn permeability with a lattice Boltzmann technique on a layered firn column using X-ray images. These authors worked out a representative volume element for permeability, going beyond the sole density as performed by Coléou et al (2001), for example.…”
Section: A Burr Et Al: X-ray Tomography Of Polar Firnmentioning
confidence: 99%
“…Other studies include the influence of microstructure, either from thick sections or Xray computed tomography on the permeability of firn at the top of the firn column Courville et al, 2007;Rick and Albert, 2004). Courville et al (2010) and Freitag et al (2002) used 3-D reconstructions of firn cube microstructure to model centimeter-scale permeability of firn using lattice Boltzmann techniques. The specific influence of microstructure on bulk properties affecting gas transport in deep firn has not been well investigated.…”
Section: S a Gregory Et Al: Impact Of Physical Propertiesmentioning
confidence: 99%
“…Knowing the depth at which air can no longer exchange with the atmosphere is pivotal for determining the gas age-ice age difference. At present-day polar sites, most studies have focused on the bulk properties of the firn, and not until the recent past have studies started to include the layered nature of the firn Courville et al, 2010;Freitag et al, 2004;Fujita et al, 2009;Horhold et al, 2011).…”
Section: Introductionmentioning
confidence: 99%